Efficacy of Cover Crops for Pollinator Habitat Provision and Weed Suppression. Issue 1 (13th January 2021) - Bryan, Casey J; Sipes, Sedonia D; Arduser, Mike; Kassim, Leila; Gibson, David J; Scott, Drew A; Gage, Karla L
Abstract: Pollinator declines have been documented globally, but little information is available about native bee ecology in Midwestern U.S. agriculture. This project seeks to optimize pollinator support and weed suppression in a 3-yr crop rotation with a fallow growing season. During fallow, one of five cover crop treatments (T1: crimson, red, and ladino clover and Bob oats [Fabales: Fabaceae - Trifolium incarnatum L., Trifolium pratense L., Trifolium repens L., and Cyperales: Poaceae - Avena sativa ]; T2: crimson clover and oats; T3: red clover and oats; T4: ladino clover and oats; T5: no cover crop; T6/control: winter wheat [Cyperales: Poaceae - Triticum aestivum ] L.) was seeded in one-half of 25 agricultural fields, whereas wheat was left unharvested in the other half as a comparison. Treatments that provide season-long floral resources support the greatest bee diversity and abundance (T1), and treatments with red clover support declining (Hymenoptera: Apidae) Bombus species (T1 and T3). Late-season floral resources may be important, yet limited (T1 and T4), and some species of agricultural weeds provide floral resources. Floral diversity may be less important than flower abundance or timing for pollinator diversity (T1–T4). Weed diversity was greatest in the no cover crop treatment (T5), least in winter wheat (T6), and intermediate in cover crop treatments (T1–T4) with no differences in weeds of economic concern. Wheat suppresses weeds but does not provide floral resources for pollinators. These results may also be applicable to marginal lands taken out of cultivation or field margin pollinator plantings in a typical corn–soybean rotation. Floral resource availability across the landscape is critical to maintain pollinator diversity.